2013
DOI: 10.2298/hemind120314048d
|View full text |Cite
|
Sign up to set email alerts
|

Buckwheat and quinoa seeds as supplements in wheat bread production

Abstract: The aim of this work was to compare the nutritional characteristics of wheat bread with the bread produced of wheat flour supplemented with quinoa and buckwheat seeds. Bread making properties of these blends were analyzed in order to investigate their ability to make moulded bread. Quinoa (Chenopodium quinoa Will.) and buckwheat seeds were grown in the vicinity of Belgrade, Serbia. The addition of pseudocereal seeds (at levels of 30% and 40%) and a selected technological process, which included hydrother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Despite a slightly bitter taste, wheat‐based bread with up to 200 g kg −1 of dehulled and washed quinoa seeds was judged to be fully acceptable to the taste, with a very pleasant aroma and flavour . These positive results were subsequently confirmed for bread with higher levels (300 and 400 g kg −1 ) of similarly treated quinoa seeds …”
Section: Sensory Properties and Acceptability Of Quinoa Food Productsmentioning
confidence: 92%
“…Despite a slightly bitter taste, wheat‐based bread with up to 200 g kg −1 of dehulled and washed quinoa seeds was judged to be fully acceptable to the taste, with a very pleasant aroma and flavour . These positive results were subsequently confirmed for bread with higher levels (300 and 400 g kg −1 ) of similarly treated quinoa seeds …”
Section: Sensory Properties and Acceptability Of Quinoa Food Productsmentioning
confidence: 92%
“…Turkut et al [ 13 ] revealed that quinoa flour might be considered a good alternative for gluten-free pan bread making. The sensory evaluation of the appearance, texture, and flavour displays the products to be good acceptable [ 14 ]. However, supplementation of wheat flour dough with quinoa flour [ 15 ] appeared in nutritionally improved bread with sensory acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a blend of buckwheat, amaranth, chickpea and quinoa flours subjected to sourdough fermentation by selected γ-aminobutyric acid (GABA)-producing strains allowed the manufacture of a bread enriched of GABA and should be considered as a promising possibility for enhancing nutritional, functional, sensory, and technological properties of bread. The addition of quinoa and/or buckwheat seeds (at levels of 30 and 40%) previously subjected to an hydrothermal process, resulted in a valuable effect on the nutritive value of the breads (Demin et al, 2013). Teff flour, despite being gluten-free, has been reported to produce high-quality leavened flatbread aging much slower than if made from other cereals, in particular sorghum (Sorghum bicolor (L.) Moench) (Taylor and Emmambux, 2008).…”
Section: Introductionmentioning
confidence: 99%